Technology Integration and English Language Instruction for Education - Pongpatchara Kawinkoonlasate (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Technological applications in education are altering how we collect information, conduct research, and share data with others. New computerized tools are changing the education community and how we pass knowledge to students. With these new tools, technology is being integrated into the classroom at larger scales every year. With more electronic resources available for teachers, new teaching methodologies are being used to improve EFL and ESL learners. The objectives of this academic paper are to acknowledge the significance of technological applications for teachers and language skill development in learners, to discuss the process of integration of these new technologies into the classroom, and review possible problems with the introduction of these new tools into the English classroom with regards to listening, Reading, Writing, and speaking. Throughout this paper, the term technological education and integration has been defined. An explanation of the use of technology is given. Previous studies and research on the use of Technologies in order to improve language learning skills in the classroom have been reviewed and discussed. Positive ways these Technologies can be used to assist students improve their English language skills are also suggested.